The Power of Machine Learning in Enhancing Digital Evidence Detection and Analysis - Mohammad Ali A. HAMMOUDEH (Communications of International Proceedings, 2025)
The fast rise of digital data brings both chances and problems for law enforcement and forensic investigators. The large amount of digital evidence can give useful information about crimes, but the high volume and complexity of this data make manual analysis hard. Machine learning (ML) algorithms have become a strong tool for automating and improving digital forensic investigations, providing benefits like better accuracy, efficiency, and scalability. This paper looks into how well ML algorithms work in finding and analyzing digital evidence, examining their ability to simplify forensic processes and discover hidden patterns in complicated datasets.
Keywords: Machine Learning; Digital Forensics; Algorithmic Detection; Forensic Analysis; Computational Techniques.